454. Barriers and Facilitators to Control of Hospital Acquired Infections in Jimma, Ethiopia. (26th November 2018) - Kenzie, Madeline; Safdar, Nasia; Abdissa, Alemseged; Yilma, Daniel; Siraj, Dawd
Abstract: Background: Given the complex, interdisciplinary nature of infection prevention, a systems approach may be useful to promote and sustain effective infection prevention practices. The Systems Engineering Initiative for Patient Safety (SEIPS) model provides a framework that can be used to identify barriers and facilitators of infection control practices and evaluate interactions between structures, processes, and outcomes. Methods: A qualitative study was done to evaluate barriers and facilitators to implementation of effective infection control practices at Jimma University Hospital in Jimma, Ethiopia. Twenty-two semi-structured interviews of hospital employees, selected by convenience sampling, were conducted to assess the five components of SEIPS framework: person, physical environment, tasks, organization and tools. The interviews were transcribed, coded for themes, and analyzed using the software Dedoose. Results: The primary facilitators to effective infection control were identified at the task, organization, and person level. Prominent themes included a manageable workload, a management system supportive of institutional feedback, sufficient budget, and positive individual attitude toward improving infection control. The primary barriers to effective infection control were found to be at the technology and tools, person, and organization levels. The major themes within these levels include poor supply chain management leading to personal protective equipment (PPE) shortages, an inconsistent and incomplete training program for employees, a lack of infection control policies, a lack of involvement of environmental services, and a nurse rotation program that increases unit staff turnover Conclusion: To address the identified barriers, possible interventions to consider should include: developing infection control policies and protocols, using these to implement a regular staff training program, incorporation of environmental services to the healthcare team, identify and train infection control team member to manage the PPE supply chain, and establishing an HAI surveillance program to better identify current risk areas as well as track progress. Disclosures: All authors: No reported disclosures.